Formation of motivation for independent learning as a factor in the success of student learning at the university - Nosatova, V. (New Collegium, 2021)
This article shows us the ways which help to form student’s skills of self-education. It analyses motives which induce future teachers to independence in the training in the university. Successful learning of students, first of all, depends on the development of their professional orientation. High professional orientation of students, readiness to consciously form professional qualities is a necessary condition for training competent professionals. However, in the first semester the student is focused on gaining a foothold as a student. As a result, there is a need to pay attention to learning motivation which affects the attitude to learning and determines the optimal course of the process of adaptation of students. Therefore, in order for students to study carefully and effectively, they must be interested in learning, show interest in it. It is well known that a large percentage of freshmen at the beginning of training feel insecurity and anxiety, which are the reason for lowering the level of demands and self-esteem of personal qualities. The experience of success-failure in the activity affects its quality and desire to continue to pay attention to it. The formation of motivation for independent learning of students eliminates inertia in the self-activation of mental activity and promotes the formation of professional motivation. Its components are: the ability to maintain and implement their own positive motives and needs in learning; knowledge of the peculiarities of the educational process in university, the main functions of various forms of education; the ability to build their activities purposefully.